2020
DOI: 10.1038/s41598-020-71132-5
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of cystoinflation to prevent bladder injury in the adhesive disease of multiple caesarean sections

Abstract: Caesarean sections carry the risk of urinary bladder injury due to formation of adhesions obscuring pelvic planes. Visualizing bladder during retro-fill (cystoinflation) makes it recognizable as it rises into the abdomen taking a tense rounded contour. We conducted a prospective randomized controlled trial to find out whether improved identification of bladder margins by cystoinflation could decrease bladder injury rate and blood loss without causing urological complications. This study included 214 healthy wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In our study we found decreased blood loss among group with filling technique as there was significantly higher post-operative HB level, lower blood loss and lower need for packed RBCS among bladder filling technique than in those with no filling technique. In the same hand Saaqib et al (12) showed a significant decrease in blood loss and blood transfusions with cystoinflation. The decrease of blood loss may suggest that adhesiolysis in correct planes due to cystoinflation contributed in the decrease of vascular injuries.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our study we found decreased blood loss among group with filling technique as there was significantly higher post-operative HB level, lower blood loss and lower need for packed RBCS among bladder filling technique than in those with no filling technique. In the same hand Saaqib et al (12) showed a significant decrease in blood loss and blood transfusions with cystoinflation. The decrease of blood loss may suggest that adhesiolysis in correct planes due to cystoinflation contributed in the decrease of vascular injuries.…”
Section: Discussionmentioning
confidence: 93%
“…They found significant lower incidence of urinary bladder injuries in patients treated with inflated urinary bladder just before cesarean section than in the other group (5.2% and 13.1%) respectively. In the same line, Saaqib et al (12) randomized controlled trial, used cystoinflation technique to inflate the bladder to prevent bladder injury in the adhesive disease of multiple caesarean sections. They found highly statistically significant difference as the bladder injury rate is very high in the control group (20%) than cystoinflation group (2.8%).…”
Section: Discussionmentioning
confidence: 99%
“…In retro-fill (cystoinflation), the bladder takes a rounded contour as it rises into the abdomen. Compared to the control group, cystoinflation group's bladder injury rate is significantly lower (2.8% compared to 20.6%) [11]. Prior to cesarean section, bladder and ureteric injuries are significantly reduced when the bladder is inflated.…”
Section: Introductionmentioning
confidence: 80%
“…However, this procedure is not standardized and may prolong the operative time, require extra expertise, and may not be suitable in an obstetrical emergency. 4 Traditionally, when bladder injury is suspected, a dye test with methylene blue is performed. 5 Although a few reports indicate that accidental bladder injury during a CD, when adequately repaired, may not be associated with complications, we advocate that any bladder injury should best be avoided when possible.…”
Section: Discussionmentioning
confidence: 99%